PERSEPSI MAHASISWA GEN Z TERHADAP GAYA KOMUNIKASI DOSEN GEN X DALAM INTERAKSI BAHASA PADA KONTEKS AKADEMIK DI PERGURUAN TINGGI - Ihramsari Akidah; Muhajir Muhajir; Izki Fikriani Amir (Universitas Negeri Makassar, 2026)
This study aims to analyze Generation Z students' perceptions of the verbal and digital communication styles of Generation X lecturers at the Muslim University of Indonesia. The study used a descriptive quantitative method involving 123 student respondents from non-exact study programs. The research procedure was carried out through several stages, namely, research administration, clustering of scientific fields, questionnaire validation, questionnaire distribution to respondents, and data analysis. The data analysis technique in this study used descriptive statistics. The analysis was carried out by calculating the mean, median, and mode values. The results showed that students gave a very positive perception of lecturers' verbal competence, especially in the aspects of language clarity and openness in two-way interactions. On the other hand, students perceived language formality and the use of jargon as less relevant, resulting in a perception gap. This study concluded that although the face-to-face competence of Generation X lecturers was very good, there was an urgency for lecturers to adapt technology-based communication strategies to create a more inclusive and effective academic climate for Generation Z students.